2023
DOI: 10.3390/molecules28020613
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Pharmaceutical Cocrystals: A Focused Review of Flavonoid Cocrystals

Abstract: Cocrystallization is currently an attractive technique for tailoring the physicochemical properties of active pharmaceutical ingredients (APIs). Flavonoids are a large class of natural products with a wide range of beneficial properties, including anticancer, anti-inflammatory, antiviral and antioxidant properties, which makes them extensively studied. In order to improve the properties of flavonoids, such as solubility and bioavailability, the formation of cocrystals may be a feasible strategy. This review di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…Solubility equilibrium is a type of dynamic equilibrium that exists when a chemical drug in the solid state is in chemical equilibrium with a solution of that compound . The cocrystal technique is used to increase the solubility of insoluble drugs and is one of the effective methods to increase their aqueous solubility. , To check whether the cocrystal technique improved the solubility of naringenin, we tested the solubility of NAR, NOR, and cocrystal 3 in pure water, phosphate buffer (pH = 6.8), and dilute hydrochloric acid solution (pH = 1.2) separately, and the results are shown in Figure . The experimental results showed that in pure water, the solubility in descending order was cocrystal 3 > NOR > NAR.…”
Section: Resultsmentioning
confidence: 99%
“…Solubility equilibrium is a type of dynamic equilibrium that exists when a chemical drug in the solid state is in chemical equilibrium with a solution of that compound . The cocrystal technique is used to increase the solubility of insoluble drugs and is one of the effective methods to increase their aqueous solubility. , To check whether the cocrystal technique improved the solubility of naringenin, we tested the solubility of NAR, NOR, and cocrystal 3 in pure water, phosphate buffer (pH = 6.8), and dilute hydrochloric acid solution (pH = 1.2) separately, and the results are shown in Figure . The experimental results showed that in pure water, the solubility in descending order was cocrystal 3 > NOR > NAR.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was very hard to identify the structure simply compared to the physical and spectroscopic data previously reported, since several monomethoxyflavones are possible. Attempted approaches to produce a single crystal directly the product or its cocrystals with coformers [ 32 , 33 ] such as isoniazid, isonicotinamide, and caffeine were fruitless. The problem was solved, to our delight, as its tetraacetate was suitable for X-ray analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids, including flavonols, flavonoids, chalcones, and proanthocyanidins, are natural active substances with significant health benefits and potential applications in healthcare and medicine [53,54]. In this study, we conducted a metabolomics analysis on the WR and RR of P. kingianum Coll.et Hemsl., and 200 flavonoid compounds were identified from these two organs.…”
Section: Discussionmentioning
confidence: 99%